The Effect of the Human Development Index (IPM) and Absorbed Labor on Economic Growth in East Java - Handini Retnowati Kusno; Himatul Fitria Ali; Shinta Lisdya Andini (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
Growth is a process towards change that is pursued continuously to improve people's welfare. Exploration of own resources needs to be optimized so that they can be used as input for independent regional economic growth. This study aims to examine the effect of HDI (Human Development Index) and Employed Labor on Economic Growth projected by GRDP (Gross Regional Domestic Product) in East Java. The data is in the form of secondary data obtained through the Central Statistics Agency (BPS) which is then processed using SPSS Version 25 software. The results show that the Human Development Index (IPM) has a significant positive influence on Economic Growth in East Java. Meanwhile, the absorbed workforce has no influence on economic growth in East Java.